Probing structures of large protein complexes using zero-length cross-linking - Rivera-Santiago, Roland F. (Methods, 2015)
Structural mass spectrometry (MS) is a field with growing applicability for addressing complex biophysical questions regarding proteins and protein complexes. One of the major structural MS approaches involves the use of chemical cross-linking coupled with MS analysis (CX-MS) to identify proximal sites within macromolecules. Identified cross-linked sites can be used to probe novel protein–protein interactions or the derived distance constraints can be used to verify and refine molecular models. This review focuses on recent advances of “zero-length” cross-linking. Zero-length cross-linking reagents do not add any atoms to the cross-linked species due to the lack of a spacer arm. This provides a major advantage in the form of providing more precise distance constraints as the cross-linkable groups must be within salt bridge distances in order to react. However, identification of cross-linked peptides using these reagents presents unique challenges. We discuss recent efforts by our group to minimize these challenges by using multiple cycles of LC–MS/MS analysis and software specifically developed and optimized for identification of zero-length cross-linked peptides. Representative data utilizing our current protocol are presented and discussed.